Inventariando os saberes culinários das comidas emblemáticas da Vila das Almas no Quilombo Saco das Almas, em Brejo/Ma: entre memórias e identidades - FERREIRA , Daciléia Lima (2021)
This dissertation addresses the culinary knowledge of emblematic foods from Vila das Almas, one of the seven communities of Quilombo Saco das Almas, which is located in Baixo Parnaíba Maranhense, in the municipality of Brejo / MA. Its general objective is to inventory the culinary knowledge of emblematic foods of Vila das Almas, based on the stories, oral narratives, events, experiences and experiences of its residents. Methodologically, it is a qualitative, bibliographic and exploratory-descriptive research divided into three stages: the first consisted of bibliographic research for the construction of the theoretical framework and the elaboration of data collection instruments. The second stage comprised the field research itself, in which we spent a year and a half in the data collection process, visiting the community, conducting interviews and non-participant observation during GEPEMADEC field activities. In the third, we prepared an inventory of the culinary knowledge of Vila das Almas based on the data collected and observed events. The residents of Vila das Almas with a minimum residence time of 20 years, among young people, adults and elderly, participated in the research. As main results we present an inventory that brings ten emblematic foods pointed out by the residents of Vila das Almas, as the main marks of the identities and memories of the community through cooking. They are foods that represent and carry the symbolisms, practices, experiences and experiences of the quilombo's culinary knowledge.